US major crops' uncertain climate change risks and greenhouse gas mitigation benefits. (28th October 2015) - Wing, Ian Sue; Monier, Erwan; Stern, Ari; Mundra, Anupriya
Abstract: We estimate the costs of climate change to US agriculture, and associated potential benefits of abating greenhouse gas emissions. Five major crops' yield responses to climatic variation are modeled empirically, and the results combined with climate projections for a no-policy, high-warming future, as well as moderate and stringent mitigation scenarios. Unabated warming reduces yields of wheat and soybeans by 2050, and cotton by 2100, but moderate warming increases yields of all crops except wheat. Yield changes are monetized using the results of economic simulations within an integrated climate-economy modeling framework. Uncontrolled warming's economic effects on major crops are slightly positive—annual benefits <4 B. These are amplified by emission reductions, but subject to diminishing returns—by 2100 reaching 17 B under moderate mitigation, but only 7 B with stringent mitigation. Costs and benefits are sensitive to irreducible uncertainty about the fertilization effects of elevated atmospheric carbon dioxide, without which unabated warming incurs net costs of up to 18 B, generating benefits to moderate (stringent) mitigation as large as 26 B (20 B).